Health education in the “new normal” after COVID-19 - Ruiz-Aquino, Mely (2021)
The effects of the COVID-19 disease pandemic demonstrated, once again, that these health/disease/promotion/prevention processes are essential for all aspects of life, both collective and individual. No other eventcould have generated as much impact as the pandemic (1), which has been manifested by the acute health, economic, social and educational crisis with global repercussions that it has left in its wake.